Comparison of the Antioxidant Potency of Four Triterpenes of Centella asiatica against Oxidative Stress - Jinyeong Lim; Hana Lee; Seonghwa Hong; Junsoo Lee; Younghwa Kim (MDPI AG, 2024)
We comparatively evaluated the antioxidant properties of key triterpenes from Centella asiatica, including asiatic acid (AA), asiaticoside, madecassic acid, and madecassoside, in several cell types, including skin fibroblasts, macrophages, hepatocytes, and endothelial cells, under conditions promoting oxidative stress. AA conferred the highest viability on Hs68 cells exposed to ultraviolet B (UVB) irradiation. Triterpene pretreatment attenuated the UVB-induced generation of reactive oxygen species (ROS) and malondialdehyde (MDA), as well as the UVB-induced depletion of glutathione (GSH) in skin fibroblasts. AA most potently inhibited UVB-induced MMP generation, resulting in increased intracellular collagen levels. Pretreatment with triterpenes, particularly AA, significantly improved cell viability and attenuated TBHP-induced levels of ROS, alanine aminotransferase, and aspartate aminotransferase in HepG2 cells. Triterpenes attenuated ROS levels and reduced MDA and GSH expression in EA.hy926 cells. In RAW264.7 macrophages, production of nitric oxide, tumor necrosis factor-α, and interleukin-6 (indicators of LPS-induced oxidative damage) was significantly reduced by treatment with any of the triterpenes. Statistical analyses of triterpene biological activities using principal component analysis and hierarchical clustering revealed that AA exerted the greatest overall influence and showed remarkable activity in Hs68 and HepG2 cells.